Serving at the 'Banking-Tables' : New Light on Acts 2-8 and the Link Between Spiritual and Economic Transformation - Harrison-Mills, Douglas (Biblical Interpretation Series, 2023)
Traditional exegesis divides scripture into two distinct economic models: the OT (Hebrew) model of blessing with a "surplus of prosperity", and the NT (Christian) model of economic collectivism with "all things in common". Using an economic perspective as an exegetical tool, the author demonstrates that this differentiation is an artificial construct. In particular, he argues that various NT Greek words and phrases in Acts, which have been rendered to describe acts of charity, should be reinterpreted to depict overtly commercial activities, including the possibility of a banking operation at the heart of the primitive church that posed a serious political and economic threat to the Jewish elite in first-century Jerusalem.